2015
DOI: 10.2196/med20.3912
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance Factors of Mobile Apps for Diabetes by Patients Aged 50 or Older: A Qualitative Study

Abstract: BackgroundMobile apps for people with diabetes offer great potential to support therapy management, increase therapy adherence, and reduce the probability of the occurrence of accompanying and secondary diseases. However, they are rarely used by elderly patients due to a lack of acceptance.ObjectiveWe investigated the question “Which factors influence the acceptance of diabetes apps among patients aged 50 or older?” Particular emphasis was placed on the current use of mobile devices/apps, acceptance-promoting/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
122
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(131 citation statements)
references
References 33 publications
(45 reference statements)
6
122
0
Order By: Relevance
“…For effective risk communication, trust and/or confidence in the source/receiver are important [30]. Our results are similar to previous studies about app use with respect to influencing factors such as ease of use, language, layout, and costs [24, 31]. These can be seen as general influencing factors for using any app.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…For effective risk communication, trust and/or confidence in the source/receiver are important [30]. Our results are similar to previous studies about app use with respect to influencing factors such as ease of use, language, layout, and costs [24, 31]. These can be seen as general influencing factors for using any app.…”
Section: Discussionsupporting
confidence: 86%
“…This will improve acceptance of the app [22]. Previous studies have been conducted to identify factors that may influence the use of mobile apps on, for instance, managing obesity [23] and diabetes mellitus [24] or preventing sexually transmitted infections and drug abuse in adolescents [25]. These studies show that app use will be influenced by factors such as ease of use, layout, and security of the data held in the app.…”
Section: Introductionmentioning
confidence: 99%
“…For patients aged 50 years or older, effort expectancy was identified as a key factor for diabetes applications [24]. The positive impact of effort expectancy on behavioural intention is supported by other studies that analysed consumer usage of health informatics [25].…”
Section: Effort Expectancymentioning
confidence: 55%
“…Health apps are downloaded and used without guidance [34]. Therefore, to raise the level of acceptance among older users, allow for personal contact persons during the initial phase of use [24] and training.…”
Section: Facilitating Conditionsmentioning
confidence: 99%
“…Although studies have demonstrated the ability of technology to improve access to care, inequality is still high between younger and older and more and less deprived populations . We need apps with elderly friendly features, as the elderly population is capable of adopting mHealth. While e‐commerce and m‐commerce have grown tremendously in China, mHealth presents more challenges in terms of pricing and regulations …”
Section: Discussionmentioning
confidence: 99%